One day at a time - Fenton, Corinne; Gardner, Marjory (Macmillan Education Australia South Yarra, Vic., 1997)
One Day at a Time by Corinne Fenton is an inspiring children's story that follows the journey of a young girl who learns to navigate life's challenges with resilience and optimism. The narrative emphasizes the importance of living in the moment and embracing each day as it comes. Through relatable experiences and heartfelt moments, the girl discovers the power of hope, the value of friendship, and the strength found in facing difficulties one step at a time. With beautiful illustrations and a gentle message, the book encourages young readers to appreciate the little joys in life and to approach each day with courage and positivity.